Fragments of Intangible Cultural Heritage of Srebrenica Refugees and Its' Returnees - Nirha Efendić (Društvene i Humanističke Studije, 2022)
During ethnographic research into newly established suburbs around Sarajevo, which are mainly inhabited by Srebrenica’s population who survived the persecution and genocide of 1995, I had the task of recording certain lifestyle changes of these refugees. This paper analyses the oral literary lyrical heritage of the Srebrenica region, ie. oral songs which were remembered mostly by women. Since I was myself one of those populations I relied on my personal experience that expanded my insight into more detailed knowledge, as well as the various circumstances that shaped the way of life of my respondents. On the other hand, the research aimed, among other things, to examine the role of Srebrenica women in the memory of the intangible cultural heritage of their region in recent times. First, I considered women’s self-organizing as a response to the genocide and the consequent absence of male family members and community leaders. Then I draw upon my research to consider the impact of these activities on collective attitudes toward the memory of the Srebrenicas' former spiritual life examining the presence of traditional and oral patterns in everyday life. The paper relies on interpretative and analytical methods of the science of literature.